Risk of secondary progressive multiple sclerosis: A longitudinal study. (January 2020) - Fambiatos, Adam; Jokubaitis, Vilija; Horakova, Dana; Kubala Havrdova, Eva; Trojano, Maria; Prat, Alexandre; Girard, Marc; Duquette, Pierre; Lugaresi, Alessandra; Izquierdo, Guillermo; Grand'Maison, Francois; Grammond, Pierre; et al.
Background: The risk factors for conversion from relapsing-remitting to secondary progressive multiple sclerosis remain highly contested. Objective: The aim of this study was to determine the demographic, clinical and paraclinical features that influence the risk of conversion to secondary progressive multiple sclerosis. Methods: Patients with adult-onset relapsing–remitting multiple sclerosis and at least four recorded disability scores were selected from MSBase, a global observational cohort. The risk of conversion to objectively defined secondary progressive multiple sclerosis was evaluated at multiple time points per patient using multivariable marginal Cox regression models. Sensitivity analyses were performed. Results: A total of 15, 717 patients were included in the primary analysis. Older age (hazard ratio (HR) = 1.02, p  < 0.001), longer disease duration (HR = 1.01, p  = 0.038), a higher Expanded Disability Status Scale score (HR = 1.30, p  < 0.001), more rapid disability trajectory (HR = 2.82, p  < 0.001) and greater number of relapses in the previous year (HR = 1.07, p  = 0.010) were independently associated with an increased risk of secondary progressive multiple sclerosis. Improving disability (HR = 0.62, p  = 0.039) and disease-modifying therapy exposure (HR = 0.71, p  = 0.007) were associated with a lower risk. Recent cerebral magnetic resonance imaging activity, evidence of spinal cord lesions and oligoclonal bands in the cerebrospinal fluid were not associated with the risk of conversion. Conclusion: Risk of secondary progressive multiple sclerosis increases with age, duration of illness and worsening disability and decreases with improving disability. Therapy may delay the onset of secondary progression.